(untitled) (Jagannath University Journal of Science, 2024)
Heat management in industries and other areas is a major issue currently worldwide. Conventional heat transfer fluids like water and ethylene glycol are not very effective. Nanofluids (NFs), composed of nanoparticles (NPs) dispersed throughout a base fluid (BF), have recently been identified as promising heat management agents for various industrial and other applications. Heat transmission is one of the many uses for AgNPs–water NFs (silver NPs (AgNPs) dispersed in water). The goal of this work was to determine the AgNPs–water NFs’ forced convective heat transfer coefficient (HTC) in laminar flow. Due to this, we present the results of the HTC study of AgNPs–water NFs in laminar flow in this paper. First, using AgNO3 as a precursor, a chemical reduction approach was used for facile synthesis of AgNPs in one pot at ambient temperature. Synthesized NPs were examined using ultraviolet-visible spectroscopy (UV-vis), X-ray diffraction (XRD), and transform electron microscopy (TEM) techniques. The average particle size obtained from TEM is 25 nm. The required quantity of AgNPs was added to the water to produce 0.5 and 1.0 vol% of AgNPs–water NFs. Next, zeta potential and dynamic light scattering (DLS), in addition to time-lapse observation and captured picture comparison, were used to assess the stability of the formulated NFs. To calculate the forced convective HTC of prepared NFs in laminar flow, a vertical shell and tube heat transfer apparatus and computer-based data recorder were used. According to the results, in comparison to BF, the HTC of 0.5 and 1.0 vol% NFs was 3.3 and 5 times greater, respectively which encourages the use of AgNPs–water NFs in industry and other heat management. Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 13−22